THE TREATMENT OF CHOLECYSTOCHOLEDOCHOLITHIASIS, COMBINED WITH JUXTAPAPILLARY DUODENAL DIVERTICULUM - Tomin, M. S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The retrospective study analysis of treatment outcomes of cholecystocholedocholithiasis, combined with juxtapapillary duodenal diverticulum (n=74), was carried out. The diagnostic and treatment algorithm was offered. It is recommended to include duodenoscopy to the complex of instrumental examination technics for patients over 50 years. When periampullary duodenal diverticulum doesn’t extend to intramural part of common bile duct with the direction of papillotomy discission, the common bile duct stones are removed in a duodenoscopy transpapillary way during a postoperative period. The presence of juxtapapillary duodenal diverticulum is an indication of conversion for open or laparoscopic choledocholithotomy.